Return to the origin to rediscover continuity: the uses of the figure or Rabbi Marshall Meyer to think about the present of the Conservative or Masorti Jewish Movement in the City of Buenos Aires - Lerner, Vanesa Cynthia (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
The aim of this article is to analyze the ways in which the actors of the Conservative Jewish Movement (also called Masorti) make use of the figure of Rabbi Marshall Meyer to think about the present. The experience of the religious leader in Argentina is part of the origin stories of the Movement, ensuring continuity and stability in the actors. The figure of Mayer temporally and generationally organizes their experiences, even in those who did not know him directly. The actors, in their different stories, refer to a ‘present past’. They use temporary markers such as “25 or 50 years ago” or “15 or 20 years ago” to narrate that past of splendor and glory, to later be able to talk about “today” and reflect on rabbinical leadership, religious projects and the youths. In this sense, I wonder: what does Meyer mean for the actors? How is the relationship between that generation and the leader related and what uses are made of him in the present? What is exposed here is part of the results of my doctoral thesis. It is a qualitative research that uses the interpretive approach from a sociological perspective. The data was collected through semi-structured interviews and participant observation between 2011 and 2020.